A magnetically driven origin for the low luminosity GRB 170817A associated with GW170817. (June 2018) - Tong, Hao; Yu, Cong; Huang, Lei
Abstract: The gamma-ray burst GR170817A associated with GW170817 is subluminous and subenergetic compared with other typical short gamma-ray bursts. It may be due to a relativistic jet viewed off-axis, or a structured jet or cocoon emission. Giant flares from magnetars may possibly be ruled out. However, the luminosity and energetics of GRB 170817A are coincident with those of magnetar giant flares. After the coalescence of a binary neutron star, a hypermassive neutron star may be formed. The hypermassive neutron star may have a magnetar-strength magnetic field. During the collapse of this hypermassive neutron star, magnetic field energy will also be released. This giant-flare-like event may explain the luminosity and energetics of GRB 170817A. Bursts with similar luminosity and energetics are expected in future neutron star-neutron star or neutron star-black hole mergers.